2020
DOI: 10.3389/fmicb.2020.01238
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Swine Fecal Specimens Across Different Farm Management Systems

Abstract: Antimicrobial use in agricultural animals is known to be associated with increases in antimicrobial resistance. Most prior studies have utilized culture and susceptibility testing of select organisms to document these phenomena. In this study we aimed to detect 66 antimicrobial resistance (AMR) genes for 10 antimicrobial agent classes directly in swine fecal samples using our previously developed antimicrobial resistance TaqMan array card (AMR-TAC) across three different swine farm management systems. This inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 51 publications
(60 reference statements)
5
14
0
Order By: Relevance
“…The disc diffusion method was carried out to detect antimicrobial resistance. The high antimicrobial-resistant level in this study was amoxicillin (comparable to ampicillin and penicillin), doxycycline (comparable to tetracycline) and trimethoprim-sulfamethoxazole following earlier reports [5,16,17]. This agreement with earlier studies might be because these earlier reports were conducted during a recent period for starting a campaign for reducing antimicrobial use in pig production in Thailand.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 90%
See 4 more Smart Citations
“…The disc diffusion method was carried out to detect antimicrobial resistance. The high antimicrobial-resistant level in this study was amoxicillin (comparable to ampicillin and penicillin), doxycycline (comparable to tetracycline) and trimethoprim-sulfamethoxazole following earlier reports [5,16,17]. This agreement with earlier studies might be because these earlier reports were conducted during a recent period for starting a campaign for reducing antimicrobial use in pig production in Thailand.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 90%
“…When pig age was classified into 3 age classes (sow, nursery and starter pig, and grower and finisher pig), it was rather obvious that the grower and finisher pigs played a crucial role in the difference in the number of antimicrobial resistance agents between the pigs in the CO and the DE farms. The highest value of number of antimicrobial resistance agents in all study farms with the highest in the CO farm in the northeastern region indicated a similar trend to the results of earlier reports [5]. In this report, a likely higher antimicrobial-resistant gene found in 3-week-old weaning piglets than their sows and 24 weeks old at the finishing stage, consistent with the higher number of E. coli, indicating the diversity of the microbiome which shifted over time during production stages.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 89%
See 3 more Smart Citations